[Foothills of Mountain Range – Caribbean Area] - (:unkn) unknown (My University, 2010)
In this vintage photograph of the foothills of a mountain range, we see the stark physical contours of the mountains - the mountains seem bear of any vegetation and the soil eroded - in the background, numerous trees in the middle ground and grasses in the foreground.
Colour: Sepia; Style: Landscape; Other: Unbordered; Undivided
Keywords: Caribbean Area; Postcards; Mountains--Caribbean Area; Trees--Caribbean Area; Palms--Caribbean Area